Semiotic Study Of The Animation Film Mother's Power: Representative Of Women's Power - Rusyda Nazhirah Yunus; Luki Aswar (International Journal of Multilingual Education and Applied Linguistics, 2024)
Research using Charles Sanders Peirce's semiotics in animated films is based on his triadic approach, namely icons, indexes, and symbols, which are used to understand the hidden meaning in every visual and narrative sign. In the context of film analysis, semiotics functions as a tool to dismantle and understand the structure and meaning contained in visual and narrative elements. This analysis can be done using Peirce's icon, index, and symbol approach. Researchers see how these signs play a role in forming the film's main theme or message. Researchers interpret the meaning of these signs in the social, cultural, or ideological context represented by the animated film. This approach is important for understanding how animated films reflect or influence social views on the themes discussed, such as the role of mothers or families. This interpretation also involves analyzing whether these signs contain social criticism or certain moral messages. Based on the results of the analysis, the audience not only sees the mother as a character but also as a symbol of inspiring strength, which can ultimately shape the audience's perception of the importance of the role of mothers in everyday life. Indirectly, the peace that occurs because there is a strong mother figure in carrying out the rebellion, the strength that was born within her because of the sad circumstances of life, the heartbreaking loss, the circumstances full of suffering. From the film it can be seen that the strength and sacrifice of a mother is extraordinary.